2010
DOI: 10.4103/0377-4929.68294
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi′s sarcoma: HIV-negative man with isolated penile localization

Abstract: Kaposi's sarcoma is the malignant proliferation of the endothelial cell vessels. Its genesis is still unclear; however, it seems to be related to the herpes virus infection (HHV-8). This neoplasia usually affects the lower limbs and the affected persons are mostly from the Mediterranean region. The exclusive penile localization of the Kaposi's sarcoma in a patient with a negative HIV serologia is exceptional. Our case is of a 73-year old patient with a negative HIV serology presenting an exclusive penile local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…There is a wide range of treatment options available after diagnosis and the evaluation of the size, localization and number of lesions were made, ranging from total excision to chemotherapy, cryotherapy, laser ablation, electrocautery, radiotherapy, interlesional or systemic injection of cytotoxic agents and alpha and beta interferon as an adjuvant therapy, photodynamic therapy and photodynamic treatment with imiquimod or nitrogen mustard. [15] Gümüşay et al [10] have administered 30 Gy palliative external radiotherapy to the scrotum of an 80-year-old HIV-negative patient with early stage scrotal KS and reported that the patient's lesions regressed by 90% following treatment. In other case-based treatments mentioned in the literature, small lesions had been usually surgically removed.…”
Section: Discussionmentioning
confidence: 99%
“…There is a wide range of treatment options available after diagnosis and the evaluation of the size, localization and number of lesions were made, ranging from total excision to chemotherapy, cryotherapy, laser ablation, electrocautery, radiotherapy, interlesional or systemic injection of cytotoxic agents and alpha and beta interferon as an adjuvant therapy, photodynamic therapy and photodynamic treatment with imiquimod or nitrogen mustard. [15] Gümüşay et al [10] have administered 30 Gy palliative external radiotherapy to the scrotum of an 80-year-old HIV-negative patient with early stage scrotal KS and reported that the patient's lesions regressed by 90% following treatment. In other case-based treatments mentioned in the literature, small lesions had been usually surgically removed.…”
Section: Discussionmentioning
confidence: 99%
“…HAART may help to reverse the injury, although, sometimes, new manifestations may arise, even using the therapy, there is the possibility of failure of therapy, or resistance to the drugs administered and even the abandonment of treatment and even the worsening of the disease. The encapsulation of anthracycline liposomes constitutes a considerable advance in SK chemotherapy [1,5,6,12,17,18,23].…”
Section: Discussionmentioning
confidence: 99%
“…KS is also an opportunistic condition and the degree of immunosuppression favors the onset of the disease as observed for other opportunistic conditions of an infectious nature related to AIDS, but it is not essential for the onset of the disease [10,12,23].…”
Section: Introductionmentioning
confidence: 99%
“…In India, the presence of KS has only been documented a total of seven times (Kumarasamy et al, 1996;Kura et al, 2008;Dongre and Montaldo, 2009;Kharkar et al, 2009;Soufiane et al, 2010;Vaishnani et al, 2010). However, caution must be given as all but one of the reported cases of KS were diagnosed solely on the H&E staining.…”
Section: Oral Diseasesmentioning
confidence: 99%